2003
DOI: 10.1021/ja0340331
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evolution of an RNA-Cleaving DNA Enzyme into an RNA Ligase Switches the Selectivity from 3‘−5‘ to 2‘−5‘

Abstract: Deoxyribozymes that ligate RNA expand the scope of nucleic acid catalysis and allow preparation of site-specifically modified RNAs. Previously, deoxyribozymes that join a 5'-hydroxyl and a 2',3'-cyclic phosphate were identified by in vitro selection from random DNA pools. Here, the alternative strategy of in vitro evolution was used to transform the 8-17 deoxyribozyme that cleaves RNA into a family of DNA enzymes that ligate RNA. The parent 8-17 DNA enzyme cleaves native 3'-5' phosphodiester linkages but not 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 28 publications
(53 reference statements)
2
57
0
Order By: Relevance
“…In round 6, the ligation activity of the pool as a whole was ~21%, which is comparable to the activity of the pools used to clone our previous Mg 2+ -dependent RNA ligase deoxyribozymes (46,47). For the BB selection, twelve rounds were performed, each with a 3-h incubation during the key step; the ligation activity was ~35% at round 12.…”
Section: In Vitro Selection Of Zn 2+ -Dependent Deoxyribozymes That Lmentioning
confidence: 64%
See 2 more Smart Citations
“…In round 6, the ligation activity of the pool as a whole was ~21%, which is comparable to the activity of the pools used to clone our previous Mg 2+ -dependent RNA ligase deoxyribozymes (46,47). For the BB selection, twelve rounds were performed, each with a 3-h incubation during the key step; the ligation activity was ~35% at round 12.…”
Section: In Vitro Selection Of Zn 2+ -Dependent Deoxyribozymes That Lmentioning
confidence: 64%
“…The use of Zn 2+ was key to this outcome, because all previous Mg 2+ -dependent deoxyribozymes that ligate RNA by reaction at a cyclic phosphate form 2′-5′ linkages (46)(47)(48)(49)(50). Others have described a Zn 2+ -dependent deoxyribozyme that cleaves 3′-5′ linkages (with formation of a cyclic phosphate), but no ligation activity was detected (17).…”
Section: Synthesis Of Native 3′-5′ Rna Linkages By Zn 2+ -Dependent Dmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that divalent metal ions accelerate the template-directed nonenzymatic ligation of two oligonucleotides possessing the terminal 5 -hydroxyl and 2 ,3 -cyclic phosphate (Flynn-Charlebois et al, 2003;Lutay et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The 2′-5′-linked nucleic acids can form duplex structures by themselves or by pairing with natural nucleic acids (10)(11)(12)(13)(14)(15). The 2′-5′ linkage substitutions in some functional RNAs retain molecular recognition and catalytic properties (16)(17)(18)(19). These discoveries suggested that the 2′-5′ linkage in nucleic acids could be an important alternative linkage during early evolution.…”
mentioning
confidence: 99%